Switchable quantum anomalous Hall effect in a ferromagnetic topological crystalline insulating NpSb monolayer. (28th July 2022) - Sun, Wenli; Li, Xinying; Li, Bingyang; Zou, Xiaorong; Huang, Baibiao; Dai, Ying; Niu, Chengwang
Abstract: The combination of band topology and magnetic order provides an exciting platform for exploring prominent topological quantum effects, such as the quantum anomalous Hall (QAH) effect, which is well known to emerge when the ferromagnetic (FM) order is introduced in two-dimensional (2D) topological (crystalline) insulators. However, a topological phase transition between QAH insulators and magnetic topological (crystalline) insulators in 2D intrinsic magnets is seldom reported. Here, in contrast to previous magnetic doping, we predict that a switchable topological phase transition between a QAH insulator and a 2D topological crystalline insulator can emerge in an intrinsic FM NpSb monolayer via strain engineering. With the spin-up and spin-down manifolds being oppositely tunable, the calculated mirror Chern number, Chern number, and nontrivial edge states clearly confirm the topological phase transition as well as the QAH effect. Moreover, we reveal the feasibility of attaining the QAH effect while strain is introduced by an appropriate substrate. These results are of great scientific interest for exploring and understanding nontrivial topology in 2D magnets.